2020 42nd Annual International Conference of the IEEE Engineering in Medicine &Amp; Biology Society (EMBC) 2020
DOI: 10.1109/embc44109.2020.9176720
|View full text |Cite
|
Sign up to set email alerts
|

Intensity Discriminability of Electrocutaneous and Intraneural Stimulation Pulse Frequency in Intact Individuals and Amputees

Abstract: Electrical stimulation of residual nerves can be used to provide amputees with intuitive sensory feedback. An important aspect of this artificial sensory feedback is the ability to convey the magnitude of tactile stimuli. Using classical psychophysical methods, we quantified the just-noticeable differences for electrocutaneous stimulation pulse frequency in both intact participants and one transradial amputee. For the transradial amputee, we also quantified the just-noticeable difference of intraneural microst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 14 publications
(22 reference statements)
4
26
1
Order By: Relevance
“…The ability to discriminate a 30-Hz difference at a 100-Hz reference with at least 75% accuracy requires a Weber fraction of 0.3 for changes in intraneural pulse frequency. This Weber fraction is consistent with those reported previously for intraneural stimulation via USEAs [46], as well as for those reported for epineural stimulation [16,24]. Thus, we speculate that with additional data the trend observed (p = 0.08) would reveal significance, even with the "no stimulation" condition removed.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The ability to discriminate a 30-Hz difference at a 100-Hz reference with at least 75% accuracy requires a Weber fraction of 0.3 for changes in intraneural pulse frequency. This Weber fraction is consistent with those reported previously for intraneural stimulation via USEAs [46], as well as for those reported for epineural stimulation [16,24]. Thus, we speculate that with additional data the trend observed (p = 0.08) would reveal significance, even with the "no stimulation" condition removed.…”
Section: Discussionsupporting
confidence: 92%
“…Prior work has documented the discriminability of intensity for peripheral nerve stimulation using classic psychophysical methods (i.e., the just-noticeable difference) for cuff electrodes [16], transverse intrafascicular multichannel electrodes [21], flat interface nerve electrodes [24] and USEAs [46]. By extrapolation of justnoticeable differences across the presumed range of perceivable stimulus intensities, these results suggest that at least 15, and possibly up to 46, different intensities could be felt by modulating stimulation frequencies between 1 and 300 Hz.…”
mentioning
confidence: 99%
“…Malik et al performed a rigorous comparison of the steady-state and full recursive Kalman filter using neural spike data and concluded that after steady-state convergence the two predictions are essentially identical (Malik et al, 2011 ). Our fast position update speeds will allow additional features to be added, including high-resolution, biomimetic, sensory feedback from intraneural (Wendelken et al, 2017 ; George et al, 2019b ) or electrocutaneous (George et al, 2020a ) stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…The Kalman filter presented by Wu et al ( 2006 ) was modified to improve stability and reduce the effort required to sustain grasping movements by using an ad-hoc latching filter (Nieveen et al, in review). External, ad-hoc thresholds were also then applied as follows and as previously described in George et al ( 2020a ):…”
Section: Methodsmentioning
confidence: 99%
“…Many researchers set the stimulation intensity based on sensation threshold (ST) [32], i.e., by multiplying ST by a predefined factor to obtain clearly perceivable sensation. However, there is no consensus in literature and different multiplication values have been used, e.g., 1.2 × ST [21], 1.5 × ST [23,33], 2 × ST [30], 3 × ST [34], as well as adding a constant value to ST (e.g., ST + 1.5 mA [35]) or some percentage of amplitude range between the sensation and discomfort thresholds (DT), e.g., using the midpoint amplitude [36] or three intermediate levels [31].…”
Section: Introductionmentioning
confidence: 99%